Mergers and acquisitions аs a variety of foreign economic activity in the context of attracting direct investments - Shmyhol, Nadiia; Pavlyuk, Tetyana (Management and Entrepreneurship: Trends of Development, 2017)
Purpose. To analyze the current state of the international market of mergers and acquisitions, to study the main trends of M&A in the modern world.Design/methodology/approach. The basic principles of the research are analysis and comparison, systematization of the obtained data and structural-functional approaches have been used.Findings. Despite the many obstacles, mergers and acquisitions in the Ukrainian economy still take place, and this gives us the motive to understand that the main positive aspect of these processes for the economy of our country is the attraction of foreign capital. Let's also note that today, the processes of transnationalization of the economy have a whole set of positive effects. Among them we will name the following: access to additional sources of financial capital, new technologies and potential of innovations, and also use of modern organizational and managerial experience. In turn, an increase in capital inflows is possible in two ways. The first way is to attract foreign direct investment, as a kind of foreign economic activity. First of all, in the form of attraction of investments of leading foreign TNCs that are directly received from a foreign investor in a subsidiary and subsidiary of TNC. Here the leading role is played by a favorable investment climate. And the second way to increase capital inflows is to make available to affiliated companies and TNC affiliates the sources of credit and investment capital used by the parent company itself when affiliates are included in the international (global) corporate financial network of the respective TNCs.Research limitations/implications. Ukraine as part of the European market could benefit from multibillion M & A deals, but one of the necessary conditions for this is a functional free market. The path to forming this market in Ukraine can be defined by three points: the current judicial system; simplifying the conditions for doing business; Elimination of corruption influence on business activity.Originality/value. Mergers and acquisitions are an integral part of economic life. These processes play a leading role both in the international economy as a whole and in the economy of any country. Also, we note that the merger and acquisition processes have an impact on the development of individual enterprises, industries, economic complexes and foreign trade activities in general